PEMBENTUKAN TIM GUBERNUR UNTUK PERCEPATAN PEMBANGUNAN (TGUPP) DALAM KONTEKS POLITIK PEMERINTAHAN DI PROPINSI DAERAH KHUSUS IBUKOTA JAKARTA - Rahmatulloh Rahmatulloh (Jurnal Ilmiah Mimbar Demokrasi, 2018)
This article analyses the formation process and position of the TGUPP (The Governor Team for Accelerating Development). The method used is literature study and documentary analysis. The results of the study show that TGUPP is part of the governor’s needs which are felt urgent. Besides TGUPP servers to oversee the strategic development programs which felt to bring broad impact on the society. Institutionally, the organization receives fund from APBD, responsible to the governor, and submits periodic reports to the governor, deputy governor, and regional secretary. In practice TGUPP cannot be separated from the dynamics of regional politics which are influenced by the interests of obtaining political support.